Efficacy and Safety of Selective Arterial Embolization in the Treatment of Aneurysmal Bone Cyst of the Mobile Spine: A Retrospective Observational Study. Issue 15 (1st August 2017) - Terzi, Silvia; Gasbarrini, Alessandro; Fuiano, Mario; Barbanti Brodano, Giovanni; Ghermandi, Riccardo; Bandiera, Stefano; Boriani, Stefano
Abstract : Study Design: A retrospective observational study. Objective: Our aim is to define the efficacy and safety of serial selective arterial embolization (SAE) in the treatment of aneurysmal bone cysts (ABCs), to explore potential treatment alternatives, and to define a therapeutic algorithm. Summary of Background Data: ABC is a benign lesion with an unpredictable behavior. Its treatment is challenging especially in poorly accessible surgical areas, such as spine and pelvis. Currently, the first-line treatment of ABC is repeated SAE until healing. Other options have been used with variable success rates. Methods: From January 2004 to September 2015, 23 patients affected by ABC of the mobile spine have been treated with SAE and prospectively followed up by computed tomographic scan and magnetic resonance imaging. Signs of neurological deficit, complications, healing of the lesion, and clinical outcomes were registered. Signs of healing are defined as peripheral sclerotic bone rim formation, decrease of the ABC mass, disappearance of the double content image, and bone formation inside the ABC mass, associated with remission of pain. Results: Twenty-three patients underwent SAE according to the protocol. Seventeen patients have healed. The number of procedures necessary to obtain healing (clinical and radiographic) varied from 1 to 10. No complication occurred during the procedure. Follow-up time ranged from 5 to 120 months after the last angiographic procedure. All 17 patients had complete relief of pain symptoms. Six patients did not respond to SAE, presenting a progressive clinical and radiographic worsening, and underwent other medical or minimally invasive treatments. Conclusion: Our study confirms the safety of SAE. The efficacy of the treatment was however lower than expected. SAE is indicated when pathological fracture or signs of cord damage are not detected. Infiltration with autologous bone marrow concentrate or administration of Denosumab is under investigation as alternative choices of treatment. Level of Evidence: 4